Pengaruh Brand Ambassador NCT Dream Dalam Membangun Brand Image Dan Dampaknya Pada Keputusan Pembelian (Survei pada Konsumen TapCash BNI di Kota Tasikmalaya) - Salsabila Putri Suharyantoa; Depy Muhamad Pauzy; Ai Kusmiati Asyiah (CV. ITTC INDONESIA, 2024)
This research aims to analyze the influenceof Brand Ambassador In Building Brand Image and their impact on Purchasing Decisions for TapCash BNI users in Tasikmalaya. The method used in this research ia a quantitative method with survey approach. The sampling technique is Nonprobability Sampling with Purposive Sampling method, the number of samples used in 100 respondents qith the criteria that they are TapCash users who lived in Tasikmalaya, especially purchase decisions of TapCash BNI. The data anaysis tool usesd is path analysis with the help of SPSS Version 25 software. The results showed that Brand Ambassador have a significant inluence on Purchasing Decisions with Brand Image as an intervening variable.